PENINGKATAN KINERJA TENAGA PENDIDIK MELALUI KEPEMIMPINAN KYAI DAN BUDAYA ORGANISASI - Bashirotul Hidayah (Fakultas Tarbiyah Institut Agama Islam Bani Fattah Jombang, 2020)
Kyai's leadership is a set of a set of abilities and personality traits, including authority, to serve as a means to convince those he leads so that they are willing and able to carry out the tasks carried out by the kyai as a leader in the salafiyyah Islamic boarding school Fatchul Ulum Pacet Mojokerto. From this understanding, it is expected that the Kyai leadership can influence the organizational culture. The purpose of this study are: (1) To describe the influence of the Kyai leadership on the performance of educators in Pondok Pesantren Salafiyyah Fatchul Ulum Pacet Mojokerto. (2) To describe the influence of organizational culture on the performance of teaching staff. (3) To describe the influence of kyai leadership and organizational culture on the performance of educators.